Historical Change of Educational Metaphors and Its Relation to Politics - Dainys, Augustinas (Vilnius University Open Series, 2020)
The article describes three metaphorically designated educational conceptions: the antique notion of the educator as a sculptor, the new age notion of the educator as a gardener, and our era’s emerging educator as a guide. All conceptions of education provide a specific answer to the problem of education, which consists of the fact that a human being is defined to be undefined, therefore the formation of a person depends on the educator. The educator as a sculptor addresses this problem by forcing a preconceived conception of reason on learners. The educator as a gardener accepts every learner and educates him or her by dealing with their individual capacities. The educator as a guide combines the educational method of the sculptor and the gardener: as a sculptor has a vision of the educational process, and as a gardener attempts that every learner walks this path himself or herself. The educational conception of the educator as a sculptor is socialist and the conception of the educator as a gardener is liberal. The educator as a guide corresponds to the emerging new conception of politics in our time, which has a task of reconciling socialism and liberalism.
Keywords: educational problem; sculptor; gardener; guide; socialism; liberalism